Young women's transitions from education to the labour market in Ethiopia: A gendered life-course perspective - Yeshwas Admasu; Gina Crivello; Catherine Porter (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We investigate the causes of the gender disparity in labour market participation in Ethiopia using iterative quantitative and qualitative longitudinal analysis through the whole childhood of the individual into early adulthood, from age 8 up to age 25. Multilevel survival analysis shows that girls have higher probability of remaining in school at all grades, and by age 22 significantly more women than men have completed high school or tertiary education. From an early age, both women and men undertake a lot of unpaid labour for their households that tends to be highly gendered, and women's work is uncounted in the current System of National Accounts definition of labour. However, women still undertake less paid work than men. Decent work for young women in rural areas remains especially limited; female job-seekers complain of poor working conditions and low pay or a mismatch with what they were trained to do in college or university. The role of social and migration networks in young people's transitions was less discernible in the quantitative findings but emerged as crucial in the qualitative analysis. Opportunities for young women in the labour market remain constrained compared with those for young men. This leads to less pressure on girls to drop out of school, and they have higher educational achievements; however, these do not translate into labour market participation. Marriage at a younger age also remains a key driver of women leaving the labour force in Ethiopia.
Keywords: B54; I25; J22; J24; O15; 330; gender; female labour force participation; Ethiopia